IMPORTANCE OF FORMATION AND DEVELOPMENT OF CREATIVITY SKILLS AMONG STUDENTS IN TEACHING GENERAL TECHNICAL SUBJECTS - Inamidinova Dilarom Kiramidinovna; Akhmadjonova Diyora (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article reveals the importance of developing students’ creative abilities based on the interactive method and modern pedagogical technologies. The main attention is paid to the improvement of the criteria and mechanisms for determining the development of students’ creative abilities. The improvement of a comprehensive methodological system for the development of students’ creative abilities by means of interactive teaching methods and technologies, the determination of the levels of development of creative abilities and evidence-based recommendations on the topic are presented.